Labor migration in Indonesia and the health of children left behind - James Ng (IZA Journal of Development and Migration, 2019)
Economic research on labor migration in the developing world has traditionally focused on the role played by the remittances of overseas migrant labor in the sending country's economy. Recently, due in no small part to the availability of rich microdata, more attention has been paid to the effects of migration on the lives of family members left behind. This paper examines how the temporary migration of parents for work affects the health outcomes of children left behind using the longitudinal data obtained from the Indonesia Family Life Survey. The anthropometric measure of the child health used, height-for-age, serves as a proxy for stunting. The evidence suggests that whether parental migration is beneficial or deleterious to the child health depends on which parent moved. In particular, migration of the mother has an adverse effect on the child's height-for-age, reducing height-for-age Z-score by 0.5 standard deviations. This effect is not seen on the migration of the father.
Keywords: I15; J61; O15; R23; 330; health; labor; migration; children; families left behind